THE ROLE OF ETHICS IN PUBLIC ADMINISTRATION: A SYSTEMATIC REVIEW OF GLOBAL PRACTICES AND CHALLENGE - Suprapti Widiasih; Faizah Julina; Sri Susanti (Penelitian dan Pengembangan Ilmu, 2024)
Ethics plays a fundamental role in public administration governance, especially in increasing accountability, transparency and public trust. This research aims to systematically analyze the role of ethics in global practice using a Systematic Literature Review (SLR) approach with the PRISMA framework. The research results show that the application of ethics strengthens accountability mechanisms, facilitates transparency, and builds public trust through good governance practices. The implications of this research provide recommendations for policy makers to integrate ethical principles in public policy to improve sustainable governance.